(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Respiratory distress syndrome (RDS) is a serious pathological condition that occurs most often in premature infants, resulting from a lack of pulmonary surfactant. This article discusses the clinical characteristics of premature infants with RDS, the severity of the disease, diagnostic methods, and treatment tactics. It also analyzes the effectiveness of modern preventive measures and treatment methods.